A new species of Sora Walker from Xizang, China (Coleoptera: Tenebrionidae: Lagriinae) - Zhou, Yong; Chen, Bin (Zootaxa, 2024)
Sora phyllopa sp. nov. is described from Mêdog County, Xizang, China. This new species is characterized by the emarginate male profemora with protuberances on the ventral surface, expanded male metatibiae, as well as dentate female sutural angle. Habitus, aedeagus, and diagnostic features of the new species are illustrated.